Rural Isolation, Small Towns, and the Risk of Intimate Partner Violence - DuBois, Kathryn O. (Journal of interpersonal violence, 2022)
Ethnographic research from the United States on gender-based violence showing that rural isolation exacerbates intimate partner violence (IPV) is at odds with estimates from nationally representative victimization surveys which indicate that the incidence of IPV in settlements conventionally characterized as rural is similar to or less than the incidence for urban settlements. One possible reason for this discrepancy?that the conventional metropolitan statistical area?based measure of settlement type fails to distinguish isolated rural areas from other nonmetropolitan places?is put to test in this study. Pooled data from 578,471 women interviewed a total of 1,672,999 times in the National Crime Victimization Survey (NCVS) between 1994 and 2015 were used in this study to consider the risk of IPV across a measure of settlement type that differentiates nonmetropolitan settlements into dispersed rural areas or residentially concentrated small towns. Logistic regression estimates of semiannual IPV prevalence were modeled using generalized estimating equations and robust standard errors to compensate for repeated measures and for the complex sample design of the NCVS. After adjusting for age, race/ethnicity, year, and time in sample, these analyses indicated that women from dispersed rural settlements had a lower semiannual risk of IPV (2.31 per 1,000 [95% confidence interval [CI] = [2.02, 2.64]]) than women from small towns (3.30 per 1,000 women [95% CI = [2.82, 3.87]]) or women from the urban core (2.60 per 1,000 [95% CI = [2.44, 2.77]]). Contrary to the ethnographic record, the results of this study indicate that women living in rural isolation are at a lower risk of IPV victimization relative to other American women and that women from small towns?the urbanized portions of nonmetropolitan counties?have been most at risk of suffering physical violence committed by an intimate partner.